Bharatiya nyaya sanhita, 2023 (45 of 2023) - Shree ram law house; Bare Act (Chandigarh Shree Ram Law House, 2024)
The Bharatiya nyaya sanhita, 2023 (45 of 2023) with comparison of changes in Indian penal code, 1860 viz-a-viz bharatiya nyaya sanhita, 2023 along with comparative chart.
Keywords: Bharatiya Nyaya Sanhita